Coupled system thermal Hydraulics/CFD models: General guidelines and applications to heavy liquid metals. (April 2021) - Pucciarelli, A.; Toti, A.; Castelliti, D.; Belloni, F.; Van Tichelen, K.; Moscardini, M.; Galleni, F.; Forgione, N.
Highlights: A classification for coupled STH/CFD applications is reported. Coupling techniques for spatial and temporal discretization are discussed in depth. Examples of application to liquid metals facilities are provided. Abstract: This work aims to review the general guidelines to be adopted to perform coupled System Thermal Hydraulics (STH)/CFD calculations. The coupled analysis is often required when complex phenomena characterized by different characteristic time and length scales are investigated. Indeed, by STH/CFD coupling the main drawbacks of both stand-alone codes are overcome, reducing the computational cost and providing more realistic solutions. A review of several works available in literature and involving different coupling approaches, codes, time-advancing schemes and application fields is given. Besides STH/CFD coupling techniques, spatial domains and numerical schemes are analysed in detail. A brief description of applications to heavy liquid metal systems is also reported; lessons drawn in the frame of these and other works are then considered in order to develop a set of good practice guidelines for coupled STH/CFD applications.